Circulating angiopoietin-like protein 2 levels and arterial stiffness in patients receiving maintenance hemodialysis: A cross-sectional study. (December 2020) - Fukami, Hirotaka; Morinaga, Jun; Okadome, Yusuke; Nishiguchi, Yoshihiko; Iwata, Yasunobu; Kanki, Tomoko; Nakagawa, Terumasa; Izumi, Yuichiro; Kakizoe, Yutaka; Kuwabara, Takashige; Horiguchi, Haruki; Sato, Michio; et al.
Abstract: Background and aims: Chronic low-grade inflammation is receiving much attention as a critical pathology that induces various aging phenotypes, a concept known as " inflammaging ". Uremic patients undergoing hemodialysis therapy show vascular aging phenotypes characterized by greater arterial stiffness and calcification compared to healthy controls of the same generation. In the current study, we investigated whether levels of inflammaging markers in the circulation were associated with vascular aging phenotypes in hemodialysis patients, as estimated by the cardio-ankle vascular index (CAVI). Methods: We conducted a multicenter cross-sectional study of 412 patients receiving hemodialysis and evaluated the relationship between circulating hs-CRP or ANGPTL2 levels, as markers of inflammaging, and CAVI. Results: Of 412 patients, 376 were analyzed statistically. While circulating hs-CRP levels had no significant association with CAVI, generalized linear models revealed that high circulating ANGPTL2 levels were significantly associated with increasing CAVI after adjustment for classical metabolic factors and hemodialysis-related parameters [β 0.63 (95%CI 0.07–1.18)]. Exploratory analysis revealed that high circulating ANGPTL2 levels were also strongly associated with increased CAVI, particularly in patients with conditions of increased vascular mechanical stress, such elevated blood pressure [β 1.00 (95%CI 0.23–1.76)], elevated pulse pressure [β 0.75 (95%CI 0.52–0.98)], or excess body fluid [β 1.25 (95%CI 0.65–1.84)]. Conclusions: We conclude that circulating levels of ANGPTL2 rather than hs-CRP are positively associated with CAVI in the uremic population and that ANGPTL2 could be a unique marker of progression of vascular aging in patients receiving hemodialysis. Graphical abstract: Image 1 Highlights: Hs-CRP and ANGPTL2 are both inflammaging-related factors. In patients receiving hemodialysis, we evaluated the relationship between cardio-ankle vascular index (CAVI) and circulating levels of hs-CRP or ANGPTL2. High circulating ANGPTL2 levels were significantly associated with CAVI, and no significant association for hs-CRP levels was found. ANGPTL2 could be a useful surrogate marker in evaluating the degree of vascular aging in patients receiving hemodialysis.